RISE: Robotics technology: driving innovation, transformation future: an inspirational journey of Associate Professor Dr Hanafiah Yussof on his pioneering work in robotics / Ts. Dr Judith Gisip - Gisip, Judith (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
Dr Hanafiah is from the College of Engineering, UiTM Shah Alam, Selangor, and has more than 18 years of experience in robotics research and development. He is also the Founder and Group CEO of Robopreneur Sdn Bhd and serves as the Chair of the IEEE Robotics & Automation Society (IEEE-RAS) Malaysia Chapter.